Foreword: Recovering the Common Good - Morris, Grant (Victoria University of Wellington Law Review, 2013)
The first "Recovering the Common Good" Conference was held in Wellington in October 2012. In this Foreword, special editor Dr Morris speaks of the meaning and importance of the topic, and of the conference papers that have been included in this Review.